Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan Dan Current Tax Expense Terhadap Manajemen Laba - Lely Suryani; Tiara Ayu Andryana (CV. ITTC INDONESIA, 2024)
This research aims to obtain empirical evidence about the influence of Tax Planning, Deferred Tax Expenses and Current Tax Expense on earnings management. This type of research uses associative quantitative research using secondary data taken from data from companies operating in the industrial sector. The sampling method uses purposive sampling using several criteria according to research needs. The samples in this research were 13 companies with a total of 65 samples of observations. Hypothesis testing is carried out using the Eviews 9 application. The results of data analysis show that simultaneously Tax Planning, Deferred Tax Expenses and Current Tax Expense affect earnings management. Meanwhile, partially it shows that Tax Planningand Current Tax Expense has an effect on earnings management, while Deferred Tax Expense has no effect on earnings management.